Establishing standards for Yonsei point in a White South African population for the treatment of gummy smile - Brandon Booysen; René H. Baron; André Uys (Wiley, 2023)
Abstract Introduction The purpose of this study is to establish the efficacy of Yonsei point in the treatment of a gummy smile in a White South African population. The accurate surface anatomy criteria in relation to the underlying musculature for the administration of Botulinum toxin injections in the treatment of gummy smile was determined. Materials and Methods Nineteen (10 males and 9 females) cadavers were selected for facial dissection. Facial profile photographs were taken before and after dissection. The before and after photographs were overlayed to determine where the pin positions should be on the dissected cadaver to determine the Yonsei point. The levator labii superioris (LLS), LLS alaeque nasi (LLSAN), zygomaticus minor, and zygomaticus major muscles were measured using a protractor and ruler, which accounted for the manual measurements. Digital measurements were measured by importing dissected images into ImageJ. Circles with a 2 cm diameter (1 cm radius) were constructed to determine whether the Yonsei point could successfully influence muscles fibers. Results Digital and manual measurements show comparable results with high correlation and reliability. Results showed that the White South African population had narrower facial musculature angles as compared with the Korean population. Conclusion Based on the selected sample, the Yonsei point is an ineffective injection site for the successful treatment of gummy smile in a White South African population.